PENGARUH KINERJA KEUANGAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PERTAMBANGAN DI ISSI PERIODE 2013-2017 - Lidia Ralina; Ari Prasetyo (Universitas Airlangga, 2019)
This study analyzed the influence of Islamic Social Reporting (ISR), Return on Asset, and Current Ratio on the value of the companies which were registered in ISSI in 2013-2017. This research used panel data regression analysis to combine time series data and cross section data. The results of the research with estimation model of Random Effect showed that ISR, ROA and CR partially had significant effects on the value of the company. ISR, ROA and CR silmutanously affect on the value of the mining companies registered in ISSI 2013-2017.Keywords: Islamic Social Reporting, Return on Asset, Current Ratio, and Firm ValueREFFERENCESArshad, R., Othman, S., & Othman, R. 2012. Islamic Corporate Social Responsibility, Corporate Reputation and Performance. World Academy of Science, Engineering And Technology (64), 1070-1074.Anzlina, Corry Winda dan Rustam. 2013.